THE ROLE OF NON-TIMBER FOREST PRODUCTS IN RURAL LIVELIHOODS - Faisal Razak; Syafiq Amir; Rina Farah (Yayasan Adra Karima Hubbi, 2025)
Non-timber forest products (NTFPs) have long been integral to the livelihoods of rural communities, providing essential resources for food, medicine, income, and cultural practices. Despite their importance, the role of NTFPs in improving rural welfare is often underexplored in scientific research. Understanding their contribution is critical for sustainable development and rural poverty alleviation. This study aims to assess the role of NTFPs in the livelihoods of rural populations, exploring their economic, social, and environmental significance. It further seeks to identify the challenges and opportunities surrounding the sustainable use of these resources. The research adopts a mixed-methods approach, combining qualitative interviews with local communities and quantitative data collection through surveys. Fieldwork was conducted in selected rural areas where NTFPs are a key resource. Data were analyzed using descriptive statistics and thematic analysis. Findings reveal that NTFPs significantly contribute to household income, particularly in communities with limited access to formal employment. They also play a vital role in maintaining cultural practices and providing food security. However, overharvesting and inadequate policy frameworks threaten their sustainability. NTFPs are crucial for rural livelihoods, but their continued availability depends on effective management strategies that balance economic needs with environmental conservation. Policy interventions should focus on promoting sustainable harvesting practices and supporting local communities in managing these resources.